Correction: Chen et al. Mandarin Recognition Based on Self-Attention Mechanism with Deep Convolutional Neural Network (DCNN)-Gated Recurrent Unit (GRU). Big Data Cogn. Comput. 2024, 8, 195 - Xun Chen; Chengqi Wang; Chao Hu; Qin Wang (Big Data and Cognitive Computing)
Missing Funding [...]